The Effect of Prefabricated Vertical Drain Length on Soft Soil Settlement (Case Study: The North Ring Road of Lamongan STA. 3+200) - Henniko Okadha; Herman Wahyudi; Yudhi Lastiasih; Sifa’ Udukha (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2025)
The North Ring Road of Lamongan Project Section I, which stretches from Sta. 0+000 to Sta. 3+265, is indicated to be built on soft silt soil. This paper discusses the effect of Prefabricated Vertical Drains (PVDs) length on the amount of settlement that occurs in soft soil. The method used was to compare the installation of PVDs at a quarter, half and three quarters of the thickness of the compressible soil layer. The varying lengths of PVDs were modeled on PLAXIS2D software. The results show that the longer PVDs are installed in the compressible soil, the greater settlement occurs.